Night music ebook A novel. - Moyes, Jojo (2021)
Now published in the United States for the first time—an early novel from the #1 New York Times bestselling author of The Giver of Stars and the forthcoming Someone Else's Shoes . Isabel Delancey, a classical violinist, has always taken her comfortable life for granted. But when her husband dies suddenly, leaving her with a mountain of debt, she and her two children are forced to abandon their home and move to the Spanish House, a now-dilapidated manor Isabel inherited in the English countryside.   With the house falling down around them, and the last of her savings disappearing fast, Isabel turns to her neighbors for help, not knowing that her mere presence there has stirred up long-standing obsessions.   As she fights to make her house a home, passions and lives collide. Isabel will discover an instinct for survival she never knew she had— and that a heart can play a new song. . . .